Development of IBL STEM Model-Based Teaching Materials Using Wordwall to Improve Students' Critical Thinking Skills - Freddy Tua Musa Panggabean; Ani Sutiani; Jamalum Purba (Jurnal Inovasi Pembelajaran Kimia (Journal of Innovation in Chemistry Education), 2024)
This study aims to develop teaching materials based on the IBL STEM model using the Wordwall application to improve students' critical thinking skills. The development model used refers to the ADDIE model with 30 students of the Chemistry Education Study Program, UNIMED as research subjects. The research instrument used an expert validation sheet and a test of students' critical thinking skills on stoichiometry material as many as 25 questions in the form of multiple choices. The results of the study indicate that teaching materials based on the IBL STEM model using the Wordwall application are feasible and effective in improving students' critical thinking skills in Stoichiometry learning. The feasibility is met qualitatively based on the assessment of material expert validators with an average total score of 4.36 (valid) and the assessment of media expert validators with an average total score of 4.32 (valid). Effectiveness is met based on the results of product implementation and evaluation results and is proven by statistical hypothesis testing (p < 0.05) with an average achievement of increasing students' critical thinking skills of 40.067 ± 9.318.